<h3>
Answer: C) 2</h3>
============================================================
Explanation:
g(x) is the inverse of f(x), which tells us that g undoes everything f(x) does.
If we input x = -6 then f(x) outputs 1
g(x) then reverses this to say that g(1) = -6. The inputs and outputs swap roles.
Moving to row 2, we see that f(-3) = 2 which reverses to g(2) = -3
We'll replace the g(2) with -3 to go from
f( g(2) )
to
f( -3 )
-3 isn't the answer, but I wanted to put it in bold to show how the replacement is happening.
From the table, we see that f(-3) = 2 which is the final answer
In other words, f(g(2)) = 2
------------------------------
Side note:
We can say that f(g(x)) = x for any number x in the domain of g(x).
As another example, g(3) = 5 and f(g(3)) = f(5) = 3.
The same works the other way around meaning that g(f(x)) = x.
Answer:
10+14=24
5+6=11
9+10=19
9+0=9
76+0=76
Step-by-step explanation:
comment how it helps
Answer: 1/22
Step-by-step explanation:
Вероятность вытащить оба белых шара есть умножение вероятностей 2-х событий:
Р(белый,белый)=Р(первым выберут белый шар)*Р(вторым выберут белый шар)
Р(первым выберут белый шар)=3/12=1/4
Но после того как выбрали белый шар , остались только 2 белых шара и всего осталось 11 шаров. Поэтому
Р(вторым выберут белый шар)= 2/11
Р(белый,белый)=1/4*2/11=2/44=1/22
Good for them ! They worked with things that are related to math
and arithmetic, they had some fun, and they learned something.
Much better than just fishing for answers on some boring website.
Answer:
a) 10 miles per hour
Step-by-step explanation: